Free Speech and Democracy in the Video Age - Chen, Alan K. (2015)
The pervasiveness of digital video image capture by large segments of the public has produced a wide range of interesting social challenges, but also presents provocative new opportunities for free speech, transparency, and the promotion of democracy. The opportunity to gather and disseminate images, facilitated by the reduced expense and easy access to camera phones and other hand-held recording devices, decentralizes political power in transformative ways. But other uses of this technology represent potentially significant intrusions on property rights and personal privacy. This tension creates a substantial dilemma for policymakers and theorists who care about both free speech and privacy. Because of these putative social interests, laws governing video image capture are becoming more widespread across a number of different regulatory regimes, from Federal Aviation Administration regulations of drone recordings to bans on recordings of police officers performing their duties to so-called Ag-Gag laws, which criminalize the video recording of incidents of animal abuse at commercial agricultural facilities. In this Article, we examine constitutional theory and doctrine as applied to emerging government regulations of video image capture and propose a framework that will promote free speech to the fullest extent possible without presenting unnecessary intrusions into privacy interests. The Article first argues that video recording is a form of expression or, at the very least, is conduct that serves as a necessary precursor of expression such that it counts as speech within the meaning of the First Amendment. We continue with the novel argument that none of the features that make video recording a form of speech apply differently when the recording takes place on private property. Next, we examine under what circumstances video recording is constitutionally protected. We claim that video recording in public places or on private property with the consent of those recorded is presumptively protected speech under the First Amendment. But we also argue that the right to record attaches even when the recording is nonconsensual and occurs on private property, as long as the material recorded is a matter of public concern. While we acknowledge that the First Amendment does not limit the enforceability of generally applicable prohibitions on access to private property, we nonetheless suggest that a recording of activity that is a matter of public concern and is done by someone who is lawfully present on that private property is protected speech. That is not to say that all regulation of such recordings violates the First Amendment, and we therefore address when countervailing governmental interests might justify limitations on the right to record, including tangible property interests and reasonable privacy expectations. Throughout this part, we draw on examples of laws regulating video recordings to suggest how our proposed model for a right to record would apply in context. The First Amendment model developed in this